Psychosociological Intervention: The Listening Construction and the Implication in Organizations - Braz, Matheus Viana; Casadore, Marcos Mariani; Hashimoto, Francisco [UNESP] (Universidade Estadual de Maringa, 2020)
Psychosociology offers a theoretical—methodological framework that is useful to the understanding and exploration of the relationships between the conflicts experienced in the current labor scenario, the suffering of the workers and the organizational contradictions. The purpose of this study is to understand how the work of listening in psychosociological interventions in organizations occurs and to elucidate the role of the implication of the intervener and the workers themselves in this context. As the authors of this work conduct psychosociological interventions, in public and private organizations, the data explored comes from their daily practices, from the 'reminiscence method of the researchers'. In addition to the chronological time and making it possible to overcome the intervention by the strict way of objectifying the behaviors, in the organizations this work includes the construction of a listening that is fulfilled in two distinct moments: 'of the reception and return to the historicity, and of the more directed elaborations to the productive activity of each worker'. Implication, on the other hand, does not represent a methodological obstacle to be neutralized, but a fundamental component to the consolidation of the bond with the workers is revealed, provided that it is recognized and duly worked out. Empathy, sensitivity, recognition of the other and their differences, overcoming ideal and crystallized models, as well as the implication in performing an effective work that opens space for critical questions, are fundamental ingredients of these interventions.
Keywords: Change management; intervention; work psychology